Installation of high-affinity Siglec-1 ligand on tumor surface for macrophage-engaged tumor suppression. (15th October 2021) - Zhang, Enkang; Wen, Shixiong; Quan, Jialiang; Han, Jiahuai; Cao, Hongzhi; Han, Shoufa
Graphical abstract: Abstract: Siglecs that binds cell surface sialoglycans are a family of immunomodulatory receptors, of which, Siglec-7 expressed on natural killer (NK) cells promotes tumor immunoevation while the role of Siglec-1 expressed on macrophages on tumor development remains largely unexplored. Herein, we selectively introduced high affinity sialoside ligands of Siglec-1 and Siglec-7 to tumor cell surface via in vivo Strain-promoted Azide-Alkyne cyclization of TCC Siaα2, 3-Lactose or FITC Siaα2, 6-Lactose with 9-azido sialic acid ( Az Sia) metabolically installed on tumor cell surface. We found that TCC Siaα2, 3-Lactose conjugated on tumor surface moderately inhibited tumor growth while FITC Siaα2, 6-Lactose promote tumor growth. These results suggest high-affinity ligand of Siglec-1 dispalyed on tumors surface provide a new perspective for tumor immunotherapy.